A conceptual idea of participatory design with BIM - Kızılkan, Muhammet Berkay; TÜRKYILMAZ, EMRAH (My University, 2019)
This study aims to investigate the participatory design by using BIM concept and how to increase the quality of life through BIM during the design and usage process. For this purpose, user participation and BIM relationship examined through examples from the world. This paper describes a BIM framework which enables designers to involve users by using information technology. It demonstrates that participatory design approach combined with BIM can make a significant contribution towards an increase in performance in building and in the quality of life.
Keywords: BIM; Participatory Design; Collaboration; User Needs